Mengkaji Perputaran Uang Bank Melalui Model Kaldor-kalecki: Tinjauan Numerik Untuk Sistem Kartu Kredit - Sehani, A; Ratianingsih, R; Puspita, J W (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2020)
Credit Card is a card payment instrument, where the cardholder's payment obligation is firstly fulfilled by the acquirer or publisher which use third party funds in the form of investments to pay the obligation payment of cardholder. These investment funds are managed as the initial fund of credit card customers. Some of the generated profits could be saved as bank deposits, while others are used for joint capital investment funds. The preview description shows the circulation of bank deposit of the credit card system which mathematically corresponds to the concept represented by Kaldor-Kalecki model. The aims of this study is that money circulation process is represented numerically by such model solution using the Runge-Kutta method. The interpretation of the numerical solution of the Kaldor-Kalecki model of the credit card system is simulated for Bank Mega's financial report data in 2017, the results shows that Bank Mega was found a decline of the number of credit card production. It could be said that the numerical solutions well represented the condition of the credit card system issued by Bank Mega. Negative values of numerical solution also reviews as period of the Bank investment